Governance Effectiveness and Economic Growth: Empirical Evidence from ASEAN - Basri (Jurnal Al-Istishna, 2025)
This study aims to analyze economic growth in the ASEAN region by examining economic indicators such as trade openness, labor force, and foreign direct investment (FDI) flows. To provide a broader perspective, an Islamic analysis is incorporated to offer a comparative view. Additionally, the study introduces a variable for government governance to evaluate its moderating effect (using Moderating Regression Analysis) on the relationship between dependent and independent variables. The research period spans from 2017 to 2022, covering ten ASEAN member countries as the sample. Secondary data sourced from the World Bank, and Our World In Data were analyzed using a panel data approach. The study's findings reveal that trade openness has a negative and insignificant effect on economic growth, the labor force has a significant positive effect, and foreign direct investment has a negative and insignificant effect. Furthermore, the Good Governance Indicator effectively moderates the impact of the labor force on economic growth. These findings provide valuable insights for policymakers and practitioners in formulating sustainable and inclusive economic development strategies in the ASEAN region. Such strategies include promoting equitable trade policies, implementing selective investment strategies, and improving governance across ASEAN member states. Moreover, this study emphasizes the importance of fostering regional cooperation among ASEAN countries to share best practices in implementing good governance principles, consistent with Islamic values, to achieve economic stability and collective prosperity